Tissue Damage in Human Cutaneous Leishmaniasis: Correlations Between Inflammatory Cells and Molecule Expression - Saldanha, Maíra Garcia; Pagliari, Carla; Queiroz, Adriano; Machado, Paulo Roberto Lima; Carvalho, Lucas; Scott, Phillip; Carvalho, Edgar M.; Arruda, Sérgio (Frontiers in Cellular and Infection Microbiology, 2020)
Cutaneous leishmaniasis (CL) is caused by the bite of the infected sand fly, which inoculates parasites of Leishmania spp and triggers an immune response. An exacerbated cutaneous inflammatory response is crucial for controlling parasite burden but can also promote tissue damage. This study aimed to characterize the populations of natural killer (NK), CD57+, CD4+, and CD8+ T cells, CD20+ B cells, as well as CD68+ macrophages, in biopsies of ulcerated CL lesions, and quantify the production of perforin+, grazyme B+, interleukin 1 beta (IL-1β+) and Tumor Necrosis Factor (TNF-α+ cells). We then correlated these parameters with necrosis, inflammation and the number of amastigotes. CD4+ T cells were positively correlated to the extent of inflammation, B cells and IL-1β+ were associated with the extent of necrosis, CD68+ macrophages and perforin were correlated with the number of amastigotes, and CD57+ NK cells was correlated to CD68+ macrophages and amastigotes. In sum, the finding suggests that the production of cytotoxic granules and cytokines by inflammatory cells contributes to tissue damage in CL lesions.